Evaluation of diastolic function in hypertensive using echocardiography - Lavanya, Yamini; Singh, Balaji Sharan; Srikanth, Sajja; Choudary, Koneru Veer Raghava (International Journal of Research in Medical Sciences, 2017)
Background: Heart failure is one of the most common causes of cardiovascular morbidity along with mortality and hypertension is the most common cause of cardiac failure. Recent studies have shown that isolated diastolic dysfunction very often accompanies hypertensive heart disease. Aims: The present study was conducted to identify the risk of cardiac failure in hypertensive individuals by evaluating diastolic function using mitral inflow velocities of echocardiography. Methods: Subjects attending cardiology outpatient department for master health check up with age between 25 to 80 years were selected. The procedure was explained and consent was obtained from the subjects. All the subjects underwent a detailed clinical examination. Height, weight and blood pressure of the subjects was measured and BMI was calculated. Two-dimensional Doppler echocardiographic examinations were performed with an ultrasonographic system (Philips iE 133 Echo Doppler). The student t test, chi square test and logistic regression analysis were used to find the influence of ejection fraction and heart rate on diastolic function. Results: The trans-mitral inflow parameters on Doppler echocardiography such as E wave deceleration time (DT), isovolumetric relaxation time (IVRT) and early to late transmitral peak flow velocities ratio (E/A) were significantly different in hypertensive subjects on treatment having normal ejection fraction, when compared to normotensive subjects. We observed a decrease in E/A ratio and increase in DT, IVRT with hypertension. Conclusions: From the present study it can be concluded that hypertension is significantly associated with diastolic dysfunction of heart, even in subjects with normal systolic function.